Pharmacological effects of fibroblast growth factor 21 are sex-specific in mice with the lethal yellow (Ay) mutation - E. N. Makarova; T. V. Yakovleva; N. Yu. Balyibina; K. O. Baranov; E. I. Denisova; A. D. Dubinina; N. A. Feofanova; N. M. Bazhan (Вавиловский журнал генетики и селекции)
Hypothalamic melanocortin 4 receptors (MC4R) regulate energy balance. Mutations in the MC4R gene are the most common cause of monogenic obesity in humans. Fibroblast growth factor 21 (FGF21) is a promising antiobesity agent, but its effects on melanocortin obesity are unknown. Sex is an important biological variable that must be considered when conducting preclinical studies; however, in laboratory animal models, the pharmacological effects of FGF21 are well documented only for male mice. We aimed at investigating whether FGF21 affects metabolism in male and female mice with the lethal yellow (Ay ) mutation, which results in MC4R blockage and obesity development. Obese C57Bl-Ay male and female mice were administered subcutaneously for 10 days with vehicle or FGF21 (1 mg per 1 kg). Food intake (FI), body weight (BW), blood parameters, and gene expression in the liver, muscles, brown adipose tissue, subcutaneous and visceral white adipose tissues, and hypothalamus were measured. FGF21 action strongly depended on the sex of the animals. In the males, FGF21 decreased BW and insulin blood levels without affecting FI. In the females, FGF21 increased FI and liver weight, but did not affect BW. In control Ay -mice, expression of genes involved in lipid and glucose metabolism (Ppargc1a, Cpt1, Pck1, G6p, Slc2a2) in the liver and genes involved in lipogenesis (Pparg, Lpl, Slc2a4) in visceral adipose tissue was higher in females than in males, and FGF21 administration inhibited the expression of these genes in females. FGF21 administration decreased hypothalamic POMC mRNA only in males. Thus, the pharmacological effect of FGF21 were significantly different in male and female Ay -mice; unlike males, females were resistant to catabolic effects of FGF21.